1978
DOI: 10.1152/ajprenal.1978.235.4.f376
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of arginine by the isolated perfused rat kidney

Abstract: In order to evaluate the renal contribution to the metabolism of arginine, we have evaluated its biosynthesis and catabolism in the isolated perfused rat kidney. The kidneys of eight male Sprague-Dawley rats were perfused with Krebs-Ringer-bicarbonate buffer containing albumin and amino acids. Twenty-five muCi of L-[guanidino-14C]arginine or 25 muCi L-[guanidino-14C]citrulline were added to the system and radiochromatograms of the perfusate were obtained at 0, 30, 60, and 90 min. Perfusate levels of urea, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 0 publications
0
44
0
1
Order By: Relevance
“…Szepesi et al [2] and Rabinowitz et al [5] showed that arginase activity is predom inant in the renal medulla, whereas Rogers et al [3] found this activity mostly in the renal cortex. Two studies have shown that small amounts of urea are produced by the kidney either in vitro [9] or in vivo [10].…”
Section: Introductionmentioning
confidence: 99%
“…Szepesi et al [2] and Rabinowitz et al [5] showed that arginase activity is predom inant in the renal medulla, whereas Rogers et al [3] found this activity mostly in the renal cortex. Two studies have shown that small amounts of urea are produced by the kidney either in vitro [9] or in vivo [10].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC has been used for the analysis of arginine and its metabolites (15,19,20). The HPLC examination of the acid-soluble substances demonstrated that the distribution of radioactive acid-soluble substances depend on the organs and the intervals after injection.…”
Section: Resultsmentioning
confidence: 99%
“…The results by HPLC showed that urea and guanidinosuccinic acid were the principal metabolites in the organs examined. Guanidinosuccinic acid, has been detected in the liver of uremia rats (21) and in the liver and kidney of normal rats (19,20), is formed from transamidination of arginine to aspartic acid (20). On the other hand, the interorgan flow of arginine is an important issue in relation to the urea cycle and critical nature of the extrahepatic economy (4).…”
Section: Resultsmentioning
confidence: 99%
“…Extracorporeal perfusion of the right kidney was performed according to a modification [18] of the procedure of NishiisutsufiUwo et al [16] and is summarized below. Donor animals were anesthetized with inactin (lOOmg/kg body weight, i.p.)…”
Section: Isolated Kidney Perfusion Technique Andmentioning
confidence: 99%